Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas IV Sekolah Dasar - Novianti, Vita; Alif Luthvi Azizah; Miranda Abung; Frida Destini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students’ mathematical problem-solving ability at SD Negeri 6 Metro Timur constituted the main issue in this study. This research aimed to determine the effect of the Realistic Mathematics Education (RME) approach on students’ mathematical problem-solving abilities, and to examine the differences in mathematical problem-solving abilities between students who received learning through the Realistic Mathematics Education (RME) approach and those who received learning through the scientific approach. This study employed a quasi-experimental method with a non-equivalent control group design. The research sample consisted of students from classes IVA and IVB, which were assigned as the control and experimental groups and selected using a purposive sampling technique. Data were collected using test and non-test techniques. The data obtained were analyzed using simple linear regression and an Independent Sample t-test. The results of the simple linear regression test showed that the Realistic Mathematics Education (RME) approach and the scientific approach influenced students’ mathematical problem-solving abilities by 66% and 61%. This finding is further supported by the results of the Independent Sample T-test indicated a significant difference in mathematical problem-solving abilities between students who received learning through the Realistic Mathematics Education (RME) approach and those who received learning through the scientific approach. Keywords: Mathematics, Problem-Solving, Realistic Mathematics Education